KEKERASAN ATAS NAMA AGAMA DAN SOLUSI KONFLIK MEMBANGUN PERDAMAIAN - Irawan, Deni (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
Religious violence is a phenomenon that cannot be seen individually as mere religious violence but must be seen as a result of the interrelationship between various factors. It becomes a shared duty that the peace and tranquility of nations, countries, and the world become a shared responsibility. The study discusses violence in the name of religion and peace-building conflict solutions. Use qualitative methods with descriptive approaches. The result is that there are several factors that cause violence in the name of religion: dogma (belief), ritual (tradition of religion), text (the sacred text of any religion), leadership (leadership), history (telling stories), and legitimated morality. As a solution to conflict on behalf of religion in an effort to foster peace, it is done through negotiation, dialogue, reconciliation, consensus, compromise, mediation, diplomacy, advocacy, and amnesty.